2017
DOI: 10.1186/s40463-017-0237-8
|View full text |Cite
|
Sign up to set email alerts
|

Practices regarding human Papillomavirus counseling and vaccination in head and neck cancer: A Canadian physician questionnaire

Abstract: BackgroundHuman papillomavirus (HPV) has recently been implicated as a causative agent in a rapidly growing number of oropharyngeal cancers. Emerging literature supports the hypothesis that HPV vaccination may protect against HPV-related head and neck cancer (HNC) in addition to HPV-related cervical and anogenital disease. While the association between HPV infection and cervical cancer is widely understood, its relation to HNC is less well known. The purpose of this study was to better understand HPV counselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
(6 reference statements)
1
12
0
Order By: Relevance
“…We also observed a lack of knowledge about the Brazilian cervical cancer screening protocol. Among ObGyn physicians, we found a better understanding of Pap test and HPV diagnosis, in agreement with Canadian studies 18,19 . As to the HPV vaccine, 94.4% of RJ physicians were aware of the recommended age, while other studies showed lower scores: in Polonia, only 24.9% 13 ; in Liguria, Italy, 73.7% 7 ; in Italy, among general practitioners, 87.0% 12 ; in Lebanon, 81.5% 20 ; and in the USA, 56.0% (family physicians) and 85.0% (pediatricians) 21 .…”
Section: Discussionsupporting
confidence: 87%
“…We also observed a lack of knowledge about the Brazilian cervical cancer screening protocol. Among ObGyn physicians, we found a better understanding of Pap test and HPV diagnosis, in agreement with Canadian studies 18,19 . As to the HPV vaccine, 94.4% of RJ physicians were aware of the recommended age, while other studies showed lower scores: in Polonia, only 24.9% 13 ; in Liguria, Italy, 73.7% 7 ; in Italy, among general practitioners, 87.0% 12 ; in Lebanon, 81.5% 20 ; and in the USA, 56.0% (family physicians) and 85.0% (pediatricians) 21 .…”
Section: Discussionsupporting
confidence: 87%
“…When surveyed, pediatricians, primary care physicians, otolaryngologists, and obstetricians/gynecologists lacked awareness of the primary tumor site (palatine and lingual tonsils), the higher prevalence in men, the sexual transmission, and the availability of a vaccine that targets HPV types associated with oropharynx cancer. 24,25 Due to this selfreported lack of knowledge, these topics often are not part of physicians' routine patient counseling about HPV vaccination. 25 Further study by the scientifi c community is ongoing in an attempt to fully understand HPV-associated oropharyngeal SCC.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…24,25 Due to this selfreported lack of knowledge, these topics often are not part of physicians' routine patient counseling about HPV vaccination. 25 Further study by the scientifi c community is ongoing in an attempt to fully understand HPV-associated oropharyngeal SCC. Clinicians should tell patients that: • HPV infection is common and does not indicate promiscuity.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…On the other hand, according to a study conducted on Canadian physicians, only 5% of primary care physicians revealed any doubt regarding the evidence supporting HPV associated head and neck cancer. 36 Although a significant difference was not found, more DP identified HPV as a risk factor for OPC, when compared to MP. Similarly, dentists showed higher overall HPV related knowledge than dental hygienists in a study examining knowledge of HPV among dentists and dental hygienists attending a regional dental conference in Florida, United States.…”
Section: Discussionmentioning
confidence: 85%